2013
DOI: 10.1128/jvi.03083-12
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of Dengue Virus Nonstructural Protein 5 Does Not Strictly Correlate with Efficient Viral RNA Replication and Inhibition of Type I Interferon Signaling

Abstract: dDengue virus (DENV) is an important human pathogen, especially in the tropical and subtropical parts of the world, causing considerable morbidity and mortality. DENV replication occurs in the cytoplasm; however, a high proportion of nonstructural protein 5 (NS5), containing methyltransferase (MTase) and RNA-dependent RNA polymerase (RdRp) activities, accumulates in the nuclei of infected cells. The present study investigates the impact of nuclear localization of NS5 on its known functions, including viral RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 38 publications
6
94
1
Order By: Relevance
“…For example, the Ebola virus VP24 protein binds to human KPNA1, -5, and -6, preventing the binding and subsequent nuclear translocation of phosphorylated STAT1, inhibiting IFN signaling (68,69), whereas the Hantaan virus N protein binds to KPNA1, -2, and -4, inhibiting the nuclear translocation and activity of NF-B (70). The results of our work and a recent study (46) suggest that nuclear localization of DENV NS5 is not strictly essential for DENV replication. However, previously, we found that mutations in DENV-2 NS5 that delay nuclear localization lead to decreased virus replication (30).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…For example, the Ebola virus VP24 protein binds to human KPNA1, -5, and -6, preventing the binding and subsequent nuclear translocation of phosphorylated STAT1, inhibiting IFN signaling (68,69), whereas the Hantaan virus N protein binds to KPNA1, -2, and -4, inhibiting the nuclear translocation and activity of NF-B (70). The results of our work and a recent study (46) suggest that nuclear localization of DENV NS5 is not strictly essential for DENV replication. However, previously, we found that mutations in DENV-2 NS5 that delay nuclear localization lead to decreased virus replication (30).…”
Section: Discussioncontrasting
confidence: 43%
“…The mutation of the A2 cluster to Ala was found to delay NS5 nuclear localization. Studies investigating the effects of mutations made to DENV-2 NS5 a/bNLS on virus replication and POL activity, using bacterially expressed NS5, have shown that only the mutation R401A/K401A (Ser-401/ Lys-402 in DENV-4) abolished virus replication and POL activity (46,62), whereas other mutations could reduce viral replication without affecting POL activity (46), highlighting the pleiotropic effects of mutations in the a/bNLS region.…”
Section: Discussionmentioning
confidence: 99%
“…Replication was determined by measuring luciferase activity in cell lysates 4, 24, 48, and 72 h after transfection. For harvest, cells were washed once with PBS and lysed by adding 200 l lysis buffer as previously described (19). Cells were frozen immediately at Ϫ70°C, and after thawing, lysates were resuspended by gentle pipetting.…”
Section: Methodsmentioning
confidence: 99%
“…The total volume of the reaction mixture was 15 l, and reactions were performed in two stages: stage 1, 15 min at 95°C; stage 2, 40 cycles of 15 s at 95°C and 60 s at 60°C. Quantities of DV RNA were calculated by using serial dilutions of known amounts of DV in vitro transcripts that were processed in parallel as previously described (19).…”
Section: Methodsmentioning
confidence: 99%
“…The activity of DENV-encoded Rluc was used as a measure for intracellular RNA replication of reporter replicons and viruses. Cells were lysed, and Rluc assays were performed exactly as previously described (33) by measuring luminescence using a Lumat LB9507 luminometer (Berthold Technologies, Bad Wildbad, Germany) upon addition of coelenterazine (1.43 M final concentration).…”
Section: Cells and Antibodiesmentioning
confidence: 99%